2015
DOI: 10.1111/omi.12146
|View full text |Cite
|
Sign up to set email alerts
|

d‐Alanine metabolism is essential for growth and biofilm formation of Streptococcus mutans

Abstract: Part of the d-alanine (d-Ala) metabolic pathway in bacteria involves the conversion of l-alanine to d-Ala by alanine racemase and the formation of d-alanyl-d-alanine by d-alanine-d-alanine ligase, the product of which is involved in cell wall peptidoglycan synthesis. At present, drugs that target the metabolic pathway of d-Ala are already in clinical use - e.g. d-cycloserine (DCS) is used as an antibiotic against Mycobacterium tuberculosis. Streptococcus mutans is the main cariogenic bacterium in the oral cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The increase in extracellular LTA in the ECM of biofilms formed by ΔdltA and ΔdltD was unexpected, thus, the absence of either dltA or dltD in the dltABCD operon may trigger an unknown compensatory pathway, causing an increase in LTA release to the matrix by these strains. Therefore, it is postulated that there could be an increase in the remodeling of the cell wall, making these genes relevant as targets in future anti-biofilm therapies, as previously suggested (Qiu et al 2015). Moreover, the D-alanization process mediated by a functional dlt operon has been shown to confer resistance to cationic antimicrobial agents in Streptococcus pneumoniae (Kovács et al 2006), but how it would affect strategies against cariogenic biofilms warrants further studies.…”
Section: Discussionmentioning
confidence: 85%
“…The increase in extracellular LTA in the ECM of biofilms formed by ΔdltA and ΔdltD was unexpected, thus, the absence of either dltA or dltD in the dltABCD operon may trigger an unknown compensatory pathway, causing an increase in LTA release to the matrix by these strains. Therefore, it is postulated that there could be an increase in the remodeling of the cell wall, making these genes relevant as targets in future anti-biofilm therapies, as previously suggested (Qiu et al 2015). Moreover, the D-alanization process mediated by a functional dlt operon has been shown to confer resistance to cationic antimicrobial agents in Streptococcus pneumoniae (Kovács et al 2006), but how it would affect strategies against cariogenic biofilms warrants further studies.…”
Section: Discussionmentioning
confidence: 85%
“…Bacterial metabolism is an important activity for biofilms; for instance, d-alanine metabolism is essential for the formation and growth of Streptococcus. 138 In addition, Lundberg et al 143 confirmed that the long-distance electrical signal conduction of bacteria in a biofilm is carried out by potassium ion channels. Moreover, diffusion of potassium ions coordinates the metabolic activities of bacteria inside and outside the biofilm.…”
Section: Nps Inhibit the Formation Of Bacterial Biofilmsmentioning
confidence: 99%
“…137 Bacterial metabolism is an important activity of biofilms: d-alanine metabolism is essential to the formation and growth of S. mutans biofilm. 138 Therefore, we hypothesized that nano-titanium dioxide inhibits the formation of biofilms, which may in turn influence the metabolism of biofilms. Generally, NPs can attack bacteria cells through multiple mechanisms, as reviewed in the following sections (Figure 4).…”
mentioning
confidence: 99%
“…In addition, the ΔdltD strain also showed a lower number of caries lesions in enamel and dentin of rats (vs. the parental strain UA159), suggesting that the product of the dltD gene could also be involved in the cariogenicity of S. mutans. This finding was expected since the dltABCD operon genes are required for the addition of D-alanine residues during LTA synthesis [19]; these residues affect bacterial adhesion to the surface and formation of biofilms [22,23,46,47]. Also, a previous in vivo study induced the expression of the dltABCD operon and demonstrated a higher occurrence of caries [48].…”
Section: Discussionmentioning
confidence: 73%